Examining the highs and lows of teacher self-efficacy for special class teachers working with learners with Autism/Autism Spectrum Disorder. (June 2022) - Ryan, Amy; Mathews, Elizabeth S.
Abstract: Background: According to data provided by the National Council for Special Education (NCSE), between 2020 and 2021, there was a 15% increase in the number of special classes specifically for learners with Autism/Autism Spectrum Disorder (A/ASD) attached to mainstream schools in the Republic of Ireland. Given the considerable growth in A/ASD classes in schools, examining the Teacher Self-Efficacy (TSE) of teachers working there enables us to identify strengths and areas for professional development (PD). Method: This paper reports the findings from an Irish study into Teacher Self-Efficacy (TSE) of teachers working in special classes for learners with A/ASD. The study involved a large sample (n = 139) of teachers responding to an online questionnaire. The questionnaire included the Autism Self-Efficacy Scale for Teachers (ASSET). Results: Analysis of the completed questionnaires reveals that the areas teachers feel least confident in are their abilities to train peer models, to teach play skills, and to translate assessment information into teaching objectives to the students. They felt most confident in their ability to use visual supports to foster student independence, to describe their student's characteristics that relate to A/ASD, and to communicate and work effectively with parents or caregivers. Conclusions: The findings of this study present implications for professional development for teachers of learners with A/ASD, namely that upskilling is needed in training peer models, play skills, and translating assessment information into teaching objectives. The results also add further evidence to the use of the ASSET as a reliable measure of assessing the Teacher Self-Efficacy for teaching students with A/ASD. Highlights: A study on teacher self-efficacy among 139 teachers in special classes for students with Autism/Autism Spectrum Disorder (A/ASD) in Ireland. A study on teacher self-efficacy among 139 teachers in special classes for students with Autism/Autism Spectrum Disorder (A/ASD) in Ireland. The Autism Self-Efficacy Scale for Teachers (ASSET) was used. The mean ASSET score of the sample was 4.38. Teachers felt least confident in: training peer models, teaching play skills, translating assessment information into teaching objectives. Teachers felt most confident in: using visual supports, describing student's characteristics, and communicating effectively with parents.